A rare case of elephantiasic pretibial myxedema with secondary cutis verticis gyrata - Aung, Phyo Zaw; Simsamer, Pacharee; Nararatwanchai, Thamthiwat (International Journal of Research in Dermatology, 2022)
A 61-year-old man with a history of thyrotoxicosis, diabetes mellitus, hypertension, and dyslipidemia presented to the dermatology outpatient clinic with bilateral non-pitting edema, asymmetrical yellowish-brown plaques, and nodules associated with some areas of hyperpigmentation, Peau’d orange appearance and elephantiasis-like skin lesions over both low legs. It was diagnosed as pretibial myxedema attributed to thyrotoxicosis. Additionally, convoluted folds and deep furrows similar to the cerebral cortical surface were seen on the forehead suggesting secondary cutis verticis gyrata (CVG) and our approach to the patient will be discussed in this case report.